Polymeric nanoparticle mediated targeted drug delivery to cancer cells - Gul-E-Saba, (Apple Academic Press, 2014)
Nanotechnology deals with synthesis, characterization, assembly and controlled shape and size at nanoscale, one-billionth of a meter (10-9 m) and has wide range of applications. Enhanced solubility, effective permeability along with target ability of nanoparticles are unique properties in therapeutics delivery of drug to cancer cells. Nanomedicine has potential to move the health care forward. Drug market for nanotechnology is estimated at 200 billion by 2015. Nanomedicines for deadly diseases such as cancer, acquired immune deficiency syndrome (AIDS), diabetes, and various other diseases are in different clinical trial phases (Kumari et al., 2009). Great advancement in microelectronics and materials science has resulted in an increase in a number of devices for diagnostics, biosensors and imaging technology, which assist rapid progress in the field of nano-carriers for drug delivery. Non-invasive imaging methods including X-ray-based computer-assisted tomography (CT), single-photon emission tomography, magnetic resonance imaging (MRI) and positron emission tomography (PET) are important tools for the detection of human cancer (Ferrari, 2005). Â© 2015 by Apple Academic Press, Inc.